Tissue-specific control of latent CMV reactivation by regulatory T cells. - Maha Almanan; Jana Raynor; Allyson Sholl; Mei Wang; Claire Chougnet; Rhonda D Cardin; David A Hildeman (PLoS Pathogens, 2017)
Cytomegalovirus (CMV) causes a persistent, lifelong infection. CMV persists in a latent state and undergoes intermittent subclinical viral reactivation that is quelled by ongoing T cell responses. While T cells are critical to maintain control of infection, the immunological factors that promote CMV persistence remain unclear. Here, we investigated the role of regulatory T cells (Treg) in a mouse model of latent CMV infection using Foxp3-diphtheria toxin receptor (Foxp3-DTR) mice. Eight months after infection, MCMV had established latency in the spleen, salivary gland, lung, and pancreas, which was accompanied by an increased frequency of Treg. Administration of diphtheria toxin (DT) after establishment of latency efficiently depleted Treg and drove a significant increase in the numbers of functional MCMV-specific CD4+ and CD8+ T cells. Strikingly, Treg depletion decreased the number of animals with reactivatable latent MCMV in the spleen. Unexpectedly, in the same animals, ablation of Treg drove a significant increase in viral reactivation in the salivary gland that was accompanied with augmented local IL-10 production by Foxp3-CD4+T cells. Further, neutralization of IL-10 after Treg depletion significantly decreased viral load in the salivary gland. Combined, these data show that Treg have divergent control of MCMV infection depending upon the tissue. In the spleen, Treg antagonize CD8+ effector function and promote viral persistence while in the salivary gland Treg prevent IL-10 production and limit viral reactivation and replication. These data provide new insights into the organ-specific roles of Treg in controlling the reactivation of latent MCMV infection.